CONDITIONS ON THE FORMATION OF ECLOGITE CLASTS IN THE LOWER PERMIAN CONGLOMERATES, ATBASHY RIDGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The petrological, mineralogical and geochemical characteristics of eclogite clasts in the Lower Permian conglomerates(the ArpaFormation) of the AtbashyRidge have been studied, and theirP-T conditions of formation have been obtained.Eclogite clasts consist mainly of garnet, omphacite, epidote, glaucophane, chlorite, white mica, quartz, and accessory minerals. Eclogites were formed from oceanic island arc and mid-ocean ridge (MORB) basalts, and experienced progressive metamorphism from epidote-glaucophane-schist facies to high pressure (T = 490– 590 °C; P = 15 kbar) eclogite facies, followed by retrograde stage in the greenschist facies. The obtained P-T conditions for the formation of eclogite clastsin the conglomerates are similar to the evolution of eclogites in the Choloktor complex.
Keywords: eclogite, P-T conditions, conglomerate, geochemistry, AtbashyRidge.